2016
DOI: 10.1103/physrevc.93.045810
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally constrained(p,γ)Y89and(n,γ)

Abstract: The nuclear level density and the γ-ray strength function have been extracted for 89 Y, using the Oslo Method on 89 Y(p, p γ) 89 Y coincidence data. The γ-ray strength function displays a low-energy enhancement consistent with previous observations in this mass region ( 93−98 Mo). Shell-model calculations give support that the observed enhancement is due to strong, low-energy M1 transitions at high excitation energies.The data were further used as input for calculations of the 88 Sr(p, γ) 89 Y and 88 Y(n, γ) 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
4
24
1
Order By: Relevance
“…Finally, our measurements at the lowest energies (i.e., around 2 MeV) also suggest the presence of a low-energy enhancement (the so-called upbend) that has been suggested by shell-model calculations to be of M1 nature [40,41]. For nuclei studied in this mass region with the Oslo method, we find a low-energy enhancement (upbend) of the γ SF [42][43][44][45][46]. The upbend has also been verified for 96 Mo using another technique [47].…”
Section: The γ -Ray Strength Functionsupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, our measurements at the lowest energies (i.e., around 2 MeV) also suggest the presence of a low-energy enhancement (the so-called upbend) that has been suggested by shell-model calculations to be of M1 nature [40,41]. For nuclei studied in this mass region with the Oslo method, we find a low-energy enhancement (upbend) of the γ SF [42][43][44][45][46]. The upbend has also been verified for 96 Mo using another technique [47].…”
Section: The γ -Ray Strength Functionsupporting
confidence: 78%
“…The main uncertainties in the present analysis stem from the E1-M1 decomposition as well as the normalization of the experimental γ SF. Note that the intrinsic model uncertainties, using all available NLD and γ SF models in TALYS, yield a factor ∼10 between the minimum and maximum (n,γ ) cross sections in this mass region [43]. Thus, although our indirect method gives a rather large error band, it is still a significant improvement compared to the range of possible values from the unconstrained model predictions.…”
Section: The Radiative Neutron Capture Cross Sectionsmentioning
confidence: 89%
“…In [23,25] it was found that the E2 transitions are of minor importance whereas the dipole transitions dominate in the low-E γ enhancement region. The first theoretical evidence of the strong enhancement at low E γ came from the shell model calculations of B(M1) values for 90 Zr, 94−96 Mo [22] and 56,57 Fe [27] where the calculated B(M1) and the γSF showed large values for low E γ .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade things have become more complicated, since measurements of the γSF [10,[14][15][16][17][18][19][20][21][22][23][24][25][26] have revealed a newly observed minimum around E γ ≃ 2 − 4 MeV, so besides the high E γ enhancement, there is also a low E γ enhancement. The first attempts to understand the low-E γ enhancement [14,15,17] used the KMF model to describe the GDR; the contribution of the giant magnetic dipole resonance to the total γSF is fitted by a Lorentzian, similarly to the E2 resonance, while the low-E γ region is described by a separate term that has a power-law parametrization.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, NLD and γ SF are nuclear properties of significance to nucleosynthesis [7] and calculations have shown that relative small changes to the overall shape of the γ SF, such as a pygmy resonance, can have an order-of-magnitude effect on the rate of elemental formation [8]. It has been shown that measured statistical properties can reliably be used to reproduce capture cross sections that were measured using other techniques [9][10][11], although further validations are needed across the nuclear chart. Additionally, NLD and γ SF can also be relevant to the design of existing and future nuclear power reactors, where simulations depend on such nuclear data [1].…”
Section: Introductionmentioning
confidence: 99%